Peningkatan Kemampuan Berpikir Kritis dan Keaktifan Belajar Materi Statistika Melalui Model Problem Based Learning Berpendekatan STEAM - Putu Novi Wipra Asti; Andriyani (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to improve students' critical thinking skills and learning liveliness on statistics material in class VIII A of SMP Negeri 1 Sukawati using the Problem Based Learning (PBL) model with a STEAM approach. This research is Classroom Action Research which consists of 2 (two) cycles, and each cycle consists of 4 stages, including planning, implementation, observation, and reflection. The data collection technique of this research is by using a critical thinking skills test, observation, and student questionnaires to assess learning liveliness. The data were analyzed quantitatively and qualitatively. The results showed that the average score of students' critical thinking skills at the initial reflection was 64, then in the first cycle was 74.25, and in the second cycle was 89.125. Based on the student response questionnaire results, the percentage of student learning liveliness during the initial reflection was 48.93%, in the first cycle, it was 70.85%, and in the second cycle, it was 91.10%. The results of this study show that applying the Problem Based Learning (PBL) model with a STEAM approach can improve critical thinking skills and student learning liveliness.